EDUKASI KESEHATAN REPRODUKSI MELALUI E-KOMIK “ANAKKU STUNTING” DALAM UPAYA PENCEGAHAN STUNTING - Khair Anwar, Khalidatul; Wulandari, Hesti; Asi, Melania (Jurnal Stunting Pesisir dan Aplikasinya, 2024)
The causes of stunting start from adolescent girls as mothers-to-be suffer from anemia, lack of nutritional intake when they are still teenagers until before marriage and pregnancy. S This affects the nutritional quality of the child he will conceive. Therefore, understanding health starting from adolescence is very important so that when planning a family, adolescents have maintained health and understand the good and bad impacts related to health. Teenagers today generally prefer something that is varied and not boring, the educational process must be designed with this in mind. The use of the right media can be one solution to increase adolescents' interest in obtaining health information. One of the media that can be used is e-comics where Indonesia is ranked second in the world for the number of comic readers with an average score of someone reading 3 comic books. Methods: quasi-experimental research with two group pre and post test design. The research sample was 40 students (20 people per group) of SMP 5 Kendari grade IX with an accidental sampling technique. The analysis used the wilcoxon test and the Mann Whitney test. Results: the results of the knowledge wilcoxon test in the experimental group showed p-value = 0.000 which means there was a significant difference in knowledge before and after the intervention. The Mann Whitney test between the two groups showed a p-value = 0.000 which means that there is an influence of education through e-comics on reproductive health knowledge in stunting prevention. Suggestion: It is hoped that the provision of health education to adolescents can utilize e-comic media so that it attracts interest in reading.